THE TRANSFORMATION OF SHARIA ACCOUNTING IN PROMOTING SUSTAINABILITY ECONOMIC GROWTH - Abdul Rahman Ramadhan (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2023)
This research aims to analyze the transformation of Islamic accounting and its impact on strengthening the sustainable economy and gain a deeper understanding of innovative Islamic accounting practices, the role of technology in driving efficiency, and their contribution to overall Islamic economic growth. In recent years, the Islamic economy has experienced significant growth in various countries. Islamic economic principles based on Islamic moral and ethical principles offer an attractive alternative to the conventional financial system. Islamic accounting has a key role in ensuring transparency, sharia compliance, and sustainable growth in the Islamic economy. This research will discuss the importance of transformation in sharia accounting practices to achieve the goal of strengthening the broader sharia economy. Sharia accounting, as one of the important elements in the Islamic economy, plays a crucial role in ensuring transparency, sharia compliance and sustainable growth. However, further research is needed to understand how transformation in sharia accounting practices can encourage the strengthening of a sustainable economy. This research is qualitative research. The data collection technique used in this research was literature review from secondary data sources in the form of books, journals, scientific articles, official invitational websites that have information relevant to research topics such as sharia accounting and economics. The data analysis technique used in this research is content analysis technique. The results of this research are expected to provide a deeper understanding of the role and contribution of sharia accounting transformation to strengthening a sustainable economy as well as contribute to science, provide practical guidance, and raise awareness about sustainability and sharia accounting among the public.